The role of education in development: an educationalist’s response to some recent work in development economics - McGrath, Simon (Taylor & Francis, 2010)
This paper delves beneath the widespread belief that education (often repackaged as human capital) is important in development to consider the role that the discipline of education plays in shaping the wider discourses of development. In particular, it will explore recent texts by important figures in development economics (Collier, Easterly, Sachs and Stiglitz) to see what they say (and don’t say) about education’s role in development and to contrast this with educationalists’ accounts. This will lead on to a consideration of what the implications of such a reading are for the field of international and comparative education. The paper concludes that the relative marginalisation of educational accounts in mainstream development thinking is a major challenge to which international and comparative education needs to respond.